Implementasi Keamanan Jaringan Menggunakan Firewall dan Intrusion Detection System (IDS) pada Infrastruktur Jaringan Skala Kecil–Menengah - Ferdi Ardiansyah sihombing; Naila Nafisa Zuhra; Lia Zahra; Rahul Alfarisyi; Hidayatun Nisa; Rafi Alfarsi Astiyanto (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Network security plays a vital role in ensuring the confidentiality, integrity, and availability of data in small- to medium-scale network infrastructures. This study aims to implement and evaluate the effectiveness of a layered network security system using a Firewall and an Intrusion Detection System (IDS). The methods employed include system design, firewall rule configuration using iptables and pfSense, deployment of IDS Snort/Suricata, traffic monitoring, and performance evaluation. The testing scenarios involve normal traffic, port scanning, brute force attempts, and simulated Distributed Denial of Service (DDoS) attacks. The results indicate that the implementation of firewall and IDS significantly enhances network protection by filtering malicious traffic, improving attack detection accuracy, and maintaining network stability. These findings suggest that the integration of firewall and IDS provides an optimal and efficient security solution for small- to medium-scale network environments.